2003
DOI: 10.1073/pnas.1432609100
|View full text |Cite
|
Sign up to set email alerts
|

Activation of innate immunity in the CNS triggers neurodegeneration through a Toll-like receptor 4-dependent pathway

Abstract: Innate immunity is an evolutionarily ancient system that provides organisms with immediately available defense mechanisms through recognition of pathogen-associated molecular patterns. We show that in the CNS, specific activation of innate immunity through a Toll-like receptor 4 (TLR4)-dependent pathway leads to neurodegeneration. We identify microglia as the major lipopolysaccharide (LPS)-responsive cell in the CNS. TLR4 activation leads to extensive neuronal death in vitro that depends on the presence of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
772
1
21

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 930 publications
(841 citation statements)
references
References 42 publications
47
772
1
21
Order By: Relevance
“…Microglia are activated following stimulation of TLR4, which in turn leads to the upregulation of several proinflammatory genes. Work in neonatal mice suggests that TLR4 is necessary for microglial activation following hypoxia/ ischemia, 14 and several groups that have shown that TLR4-deficient mice have better neurological outcomes following experimental stroke. 78 -81 How TLRs are activated in stroke is not precisely known, but endogenous ligands include hyaluronic acid, fibronectin, heat shock proteins (HSP), and heparin sulfate.…”
Section: Toll-like Receptors and High-mobility Group Box 1 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia are activated following stimulation of TLR4, which in turn leads to the upregulation of several proinflammatory genes. Work in neonatal mice suggests that TLR4 is necessary for microglial activation following hypoxia/ ischemia, 14 and several groups that have shown that TLR4-deficient mice have better neurological outcomes following experimental stroke. 78 -81 How TLRs are activated in stroke is not precisely known, but endogenous ligands include hyaluronic acid, fibronectin, heat shock proteins (HSP), and heparin sulfate.…”
Section: Toll-like Receptors and High-mobility Group Box 1 Proteinmentioning
confidence: 99%
“…It is important, however, to place this approach in context. Although there is now strong evidence that the inflammatory response can exacerbate ischemic injury, [13][14][15][16][17][18] there is also evidence that some aspects of the inflammatory response are important for tissue repair. These aspects include phagocytosis of cell debris, remodeling of the extracellular matrix, and the release of cytokines and trophic factors.…”
Section: Introductionmentioning
confidence: 99%
“…It is well described that TLR4 is involved in neurodegeneration 12, 14. It was also found that TLR4‐dependent microglial activation mediates spinal cord ischemia–reperfusion injury 11.…”
Section: Resultsmentioning
confidence: 95%
“…TLR3 also causes downregulation of TLR4 17. TLR4 has been shown to trigger neuronal degeneration and to be involved in several kinds of neurological disorders 12, 14, 15. TLR3 activation with the synthetic RNA analogue poly(I:C) and simultaneous TLR4 downregulation have been described as protective against ischemia– reperfusion injury of the spinal cord 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation